Hubungan kepuasan kerja dan komunikasi organisasi dengan kinerja pegawai Rumah Sakit Intan Medika Lamongan - Faizatul Ummah; Rahayu Ainun Khofifah; Ari Kusdiyana (MEDIA ILMU KESEHATAN, 2023)
Background: Performance is the way employees work in a company during a certain period. A company that has employees with good performance is likely to have good company performance. Objective: To determine the relationship between job satisfaction and organizational communication with employee performance at Intan Medika Hospital.Methods: A correlational research design with a cross-sectional approach and the method of proportionate stratified random sampling was used. A total of 62 employees who had been working for more than 1 year were selected as the research sample. Data were collected using a closed questionnaire in April-May 2023, and analyzed using chi-square and logistic regression.Results: The multivariate analysis results, used logistic regression, indicate that the organizational communication variable has the most dominant influence with a value of Exp(B) = 4.543 compared to the job satisfaction variable, which has an Exp(B) value of 2.803..Conclusion: The organizational communication variable has the most dominant influence on the performance of employees. Management can provided a meeting program involving all employees to better accommodate organizational communication.